Therapeutic management of the enzymatic debriding agent Nexobrid® in the burn patient - Enrique Salmeron-Gonzalez; Elena García-Vilariño; Alberto Sánchez-García; Abel Llinás-Porte; M Dolores Pérez- (Wolters Kluwer Medknow Publications, 2018)
Enzymatic debridement with Nexobrid® is a recently appeared resource, which allows a selective elimination of burned tissues with one single application, becoming a new resource in the therapeutic arsenal of the burn surgeon. In this article, we expose our experience with this product, and through a representative case, we explain the management of these patients performed in our burns unit, in consonance with national and international consensus.